(untitled) (Research, Society and Development, 2023)
This study aimed to analyze the prevalence of self-medication among academics in the health area of a higher education institution. This is a cross-sectional study, whose sample included 585 students of the courses of Nursing, Aesthetic, Physiotherapy, Physical Education, Biomedicine and Veterinary Medicine. Data were collected through a semi-structured questionnaire. For each of the responses, the raw frequency, prevalence estimates, and their appropriate proportions (%) were presented. To analyze the differences in prevalence according to self-medication in the last year, prevalence ratios were estimated. Of the total, 543 (92.8%) participants had already practiced self-medication at some point in their lives and most of these did not follow the instructions on the package insert. The most used class of drugs was anti-inflammatory; In relation to the most frequent health problems, the flu/cold predominated. The reasons that most induced self-medication were practicality and convenience; In relation to the main influencers of this practice, relatives, neighbors and friends were evident. The nursing course had a higher prevalence of self-medication. In terms of course periods, seniors practiced the most compared to freshmen. It is concluded that self-medication in academics in the health area should be less frequent since during their training they have disciplines in their curriculum matrix that increase their knowledge and demonstrate the risks of this practice. It is necessary to address educational measures related to the subject throughout graduation.